A Study on digital Journalism in Brazil - Mielkniczuk, Luciana; Quadros, Claudia Irene; Barbosa, Suzana (Brazilian journalism research, 2006)
Who are the precursors of digital journalism research in Brazil? How many theses and dissertations have already been presented on this topic? What is the proﬁ le of these publications? These are some of the questions that we intend to answer in this article which proposes to outline a preliminary survey of the studies carried out during the ﬁ rst decade of the development of this journalistic specialty in the country. Our assumption is that there are four research clusters located in the Northeastern, Central-Western, Southeastern and Southern Regions of the country.